Prosedur Transaksi di Pasar Modal (Sukuk) Perspektif Ekonomi Syariah - Andrisal; Ihsan, Budi; Mardian, Husni (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
The government and regulators play a crucial role in the development of the sukuk market. The government can provide support through favorable fiscal and monetary policies, as well as incentives for sukuk issuers. Meanwhile, regulators are responsible for establishing a clear and comprehensive regulatory framework and overseeing activities in the sukuk market. Despite its rapid growth, the sukuk market still faces several challenges, such as the lack of standardized sukuk products across different countries, low levels of Islamic financial literacy among the public, and commodity price fluctuations that may affect sukuk performance. However, the market holds significant growth potential, especially with the increasing awareness of the importance of sustainable and ethical investments. This study employs a systematic literature review approach to analyze and synthesize existing knowledge on transaction procedures in the capital market (sukuk) from an Islamic economic perspective. This method was chosen for its ability to provide a comprehensive overview of the research topic, identify gaps in the existing literature, and highlight future research directions. The findings of this study explain that sukuk represents a legal document reflecting participation in equity or debt ownership of a transferable asset, with either a long-term or permanent nature. Sukuk investment consists of certificates indicating ownership rights with values equivalent to shares. In the event of a dispute where consensus through deliberation cannot be reached, resolution may be sought through dispute resolution institutions such as the Religious Court or the National Sharia Arbitration Board of the Indonesian Ulema Council.